Flight to quality?. Issue 1 (2nd March 2015) - Fuerst, Franz; McAllister, Patrick; Sivitanides, Petros
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the effect of the crisis on the pricing of asset quality attributes. This paper uses sales transaction data to examine whether flight from risk phenomena took place in the US office market during the financial crisis of 2007-2009. Design/methodology/approach – Hedonic regression procedures are used to test the hypothesis that the spread between the pricing of low-quality and high-quality characteristics increased during the crisis period compared to the pre-crisis period. Findings – The results of the hedonic regression models suggest that the price spread between Class A and other properties grew significantly during the downturn. Research limitations/implications – Our results are consistent with the hypothesis of an increased price spread following a market downturn between Class A and non-Class A offices. The evidence suggests that the relationships between the returns on Class A and non-Class A assets changed during the period of market stress or crisis. Practical implications – These findings have implications for real estate portfolio construction. If regime switches can be predicted and/or responded to rapidly, portfolios may be rebalanced. In crisis periods, portfolios might be reweighted towards Class A properties and in positive market periods, the reweighting would be towards non-Class A assets. Social implications – The global financial crisis has demonstrated that real estate markets play a crucial role in modern economies and that negative developments in these markets have the potential to spillover and create contagion for the larger economy, thereby affecting jobs, incomes and ultimately people's livelihoods. Originality/value – This is one of the first studies that address the flight to quality phenomenon in commercial real estate markets during periods of financial crisis and market turmoil.